2021
DOI: 10.1097/qco.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use in central nervous system infections

Abstract: Purpose of review Central nervous system (CNS) infections are associated with high rates of morbidity and mortality. The purpose of this review is to summarize current antimicrobial therapies, as well as, updates in the management of community-acquired meningitis and healthcare-associated meningitis and ventriculitis. Recent findings Due to the increasing rates of multidrug resistant and extensively-drug resistant organisms, available antimicrobials are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 89 publications
0
2
0
1
Order By: Relevance
“…Several in vitro and clinical studies have suggested the clinical benefits of adopting polymyxin–drug combination therapy, especially polymyxin plus meropenem, with synergistic killing against MDR/XDR gram-negative bacteria [ 36 – 39 ]. Although meropenem is recommended as the main empirical treatment for healthcare-associated ventriculitis and meningitis against gram-negative bacteria [ 40 ], resistance may lead to delayed treatment effectiveness and adverse outcomes. This study found no beneficial results for the combination of polymyxin B and carbapenems, even when carbapenem therapy was optimized, such as increasing the dose and extending the infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and clinical studies have suggested the clinical benefits of adopting polymyxin–drug combination therapy, especially polymyxin plus meropenem, with synergistic killing against MDR/XDR gram-negative bacteria [ 36 – 39 ]. Although meropenem is recommended as the main empirical treatment for healthcare-associated ventriculitis and meningitis against gram-negative bacteria [ 40 ], resistance may lead to delayed treatment effectiveness and adverse outcomes. This study found no beneficial results for the combination of polymyxin B and carbapenems, even when carbapenem therapy was optimized, such as increasing the dose and extending the infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Los factores epidemiológicos, biomarcadores, serologías y las profilaxis recibidas son de gran utilidad para orientar la terapia empírica 162 . En adultos IS con sospecha de meningitis la terapia antimicrobiana empírica debe ser dirigida contra L. monocytogenes con ampicilina más cobertura estándar para S. pneumoniae y BGN que incluya P. aeruginosa con una cefalosporina de 4º generación como cefepime o un carbapenémico 163 . En niños, la terapia antimicrobiana debe ser de amplio espectro, usualmente basados en β-lactámicos, con cefalosporinas de tercera generación más ampicilina (que adiciona cobertura para L. monocytogenes), con o sin vancomicina, de acuerdo a la epidemiología de la resistencia in vitro de S. pneumoniae en la comunidad 107 .…”
Section: Terapia De Las Infecciones Del Sistema Nervioso Centralunclassified
“…For several antibiotics, IT use has been reviewed [ 8 , 9 , 10 ]. The range of doses administered intrathecally is quite broad.…”
Section: Introductionmentioning
confidence: 99%